Cellular effects of glycine and trehalose air-polishing powders on human gingival fibroblasts in vitro - Weusmann, Jens; Deschner, James; Imber, Jean-Claude; Damanaki, Anna; Leguizamón, Natalia D. P. [UNESP]; Nogueira, Andressa V. B. (Springer Nature, 2022)
Objectives: Air-polishing has been used in the treatment of periodontitis and gingivitis for years. The introduction of low-abrasive powders has enabled the use of air-polishing devices for subgingival therapy. Within the last decade, a wide range of different low-abrasive powders for subgingival use has been established. In this study, the effects of a glycine powder and a trehalose powder on human gingival fibroblasts (HGF) were investigated. Methods: HGF were derived from three systemically and periodontally healthy donors. After 24 h and 48 h of incubation time, mRNA levels, and after 48 h, protein levels of TNFα, IL-8, CCL2, and VEGF were determined. In addition, NF-κB p65 nuclear translocation and in vitro wound healing were assessed. Statistical analysis was performed by ANOVA and post hoc Dunnett’s and Tukey’s tests (p < 0.05). Results: Glycine powder significantly increased the expression of proinflammatory genes and showed exploitation of the NF-κB pathway, albeit trehalose powder hardly interfered with cell function and did not trigger the NF-κB pathway. In contrast to trehalose, glycine showed a significant inhibitory effect on the in vitro wound healing rate. Conclusion: Subgingivally applicable powders for air-polishing devices can regulate cell viability and proliferation as well as cytokine expression. Our in vitro study suggests that the above powders may influence HGF via direct cell effects. Trehalose appears to be relatively inert compared to glycine powder. Clinical relevance: With the limitations of an in vitro design, our study suggests that in terms of cell response, trehalose-based air-polishing powders show a reduced effect on inflammation.
Keywords: Air-polishing; Cell biology; Glycine; Periodontology; Trehalose